Geochemistry and Paleoredox Conditions of the Carbonate Reservoir Khasib Formation in East Baghdad Oilfield-Central Iraq - Ali, Rana Abbas (Journal of Petroleum Research and Studies, 2023)
The carbonate of Khasib Formation in East Baghdad Oilfield, Central Iraq was geochemically investigated to interpret paleoredox conditions and source of rare earth elements (REEs) based on major, trace, and REEs geochemistry. SiO2 and Al2O3 concentrations are nearly the same in both wells, while CaO content just hardly differs between the EB10 and EB81 cores. The EB10 Well has higher concentrations of Th, Y, and Zr than the EB81 Well. However, both the ∑REE of EB10 (1.969-35.35, n=23) and EB81 (9.59-24.88, n=20) wells have low total REE content. These results show that the Khasib Formation’s carbonate sedimentation contains seawater-like marine carbonate and PAAS-normalized REE + Y patterns accompanied by 1- light REE depletion (NdN/YbN= 0.40–0.95, n=23, and 0.54–0.90, n=20, respectively), 2- both positive to negative Ce anomalies (Ce/Ce*= 0.28-1.07, n=23; 0.39-1.76, n=20, respectively), as well as the 3-superchondritic Y/Ho ratio (23.25-57.5, n=23; 18.0-53.0, n=20, respectively). The terrigenous contribution, paleoredox conditions, and scavenging mechanisms were responsible for the observed variations in Ce components and Ce anomalies in the investigated cores. The rising U contents in the limestones (1.62-4.72 ppm) and authigenic U (0.66-4.44 ppm) indicate that dysoxic conditions were present when they were deposited. Further evidence from geochemical data suggests that diagenetic processes may be responsible for the positive Eu anomalies found in limestones. This implies that the Khasib Formation limestones may have kept their original seawater-like REE patterns. Due to trace amounts of detrital materials in certain specimens, there is identified variability in the REE + Y pattern and REE content. The current study shows that the limestones still display their original seawater-like patterns as long as shale contamination was minimal, and they act as a proxy for seawater.